Development of Interactive E-Module Chemistry Magazine Based on Kvisoft Flipbook Maker for Thermochemistry Materials at Second Grade Senior High School - Sri Saraswati; Roza Linda; Herdini Herdini (Journal of Science Learning, 2019)
This investigation aims to develop an interactive e-module chemistry magazine-based teaching material based on Kvisoft Flipbook Maker on thermochemistry for Senior High School grade XI/MA level. The research design is a development research (Research and Development) with Plomp’s model. The object of the research is the e-module inter-addictive chemistry magazine based on Kvisoft Flipbook Maker. The data instrument collection is a validation sheet form that is given to four validators and user response sheets to two chemistry subject teachers and 30 students of Senior High School grade XI focusing on Science Class. The data analysis technique is by calculated the percentage score of the validation assessment and user response. The results revealed that the developed e-module interactive chemistry magazine based on Kvisoft Flipbook Maker filled out the valid criteria by the material validators based on content substance assessment aspect with a percentage 88.89% and learning design 97.22% and by the media validators based on display (visual communication) with a percentage96.88% and software utilization 100%. While the User responses based on the teachers' and students’ responses were in very good criteria with each score 92.61% and 86.80%.